Mechanisms of resilient iron-based nanomaterials resisting environmental disturbances in arsenic-contaminated soil remediation - Bowen Fan; Zhiwei Lei; Jialin Chi; Xiangjun Meng; Kai Liu; Xiaomin Li; Liping Fang; Fangbai Li (Journal of Hazardous Materials, 2026)

Multi-task perception and three-dimensional picking point localization method for grapes based on structural constraints and geometric analysis - Xinzhao Zhou; Xiangjun Zou; Hewei Meng; Fengyun Wu; Shang Chen; Xiwen Luo (Computers and Electronics in Agriculture, 2025)

A study on the subsidence movement and stress evolution characteristics of unequally thick bedrock overburden under the extremely thick loose layer - You Li; Xiangjun Meng; Guangchao Zhang; Guanglei Zhou; Renbao Zhao; Shuiquan Chen; kai Lv (Journal of Cleaner Production, 2025)

Shear strength indices predication model for coarse-grained soil based on particle gradation and moisture content information - Tiantao Li; Jingjing Tian; Xiangjun Pei; Jian Guo; Mingyang Chen; Yuan Xue; Minghui Meng (Bulletin of Engineering Geology and the Environment, 2025)

Zinc-doped nickel sulfide/nickel hydroxide heterostructures for efficient and robust selective glucose oxidation reaction - Chi Zhang; Chunjian Xu; Linrui Yang; Xinyue Tao; Jianyi Liu; Rui Su; Xiangjun Meng; Ruoxi Yang; Dongfang Xue; Kaitian Zheng (Chemical Engineering Journal, 2025)

Enhanced co-production of H2 and formic acid via Ni-facilitated Cu+/Cu2+ cycling in an industry-level hybrid water splitting system - Xinyue Tao; Rui Su; Xiangjun Meng; Dongfang Xue; Chi Zhang; Zhaoyu Feng; Kaitian Zheng; Chunjian Xu (Chemical Engineering Journal, 2024)

Nested transformer decoder using dense skip-connections for change detection in high-resolution remote sensing image - Xiangjun Meng; Yonghong Song; Guofu Li (International Journal of Remote Sensing, 2024)

A robust and low-cost blended-fiber-based evaporator with high efficiency for solar desalination - Qianqian Liu; Xiangjun Liu; Ge Chen; Pei Feng; Yucheng Xiong; Meng An; Cheng Shao; Xiongfei Zhu; Renzong Wang; Jianshi Sun; Jisheng Sun; Chunfang Guo; et al. (Desalination, 2024)

A generic F-doped strategy for biomass hard carbon to achieve fast and stable kinetics in sodium/potassium-ion batteries - Bin He; Liangming Feng; Guang Hong; Liuchao Yang; Qian Zhao; Xiangjun Yang; Siyi Yin; Yan Meng; Dan Xiao; Yujue Wang; Jie Ai (Chemical Engineering Journal, 2024)

Myeloma extracellular vesicle-derived RAGE increases inflammatory responses and myotube atrophy in multiple myeloma through activation of the TLR4/NF-κB p65 pathway - Yue Wu; Xingchen Yao; Xiangjun Shi; Ziyu Xu; Jie Ren; Ming Shi; Meng Li; Junpeng Liu; Xinru Du (Apoptosis, 2024)

Radial growth responses of Larix gmelinii to drought events in dry and wet areas of northern temperate forests - Haibo Du; Lulu Xu; J. Julio Camarero; Paolo Cherubini; Mai-He Li; Hong S. He; Xiangjun Meng; Zhengfang Wu (Dendrochronologia, 2024)

Frequent dry-wet cycles promote debris flow occurrence: Insights from 40 years of data in subtropical monsoon region of Sichuan, China - Jierui Li; Basanta Raj Adhikari; Xiaoli Ding; Shaolin Wu; Xiangrui Meng; Zhipan Niu; Xiangjun Pei; Yu Zhan; Baofeng Di (CATENA, 2024)

Superior energy-storage performances achieved in NaNbO3-based antiferroelectric ceramics by phase-structure and relaxation regulation - Xiangjun Meng; Zhengyi Yang; Ying Yuan; Bin Tang; Shuren Zhang (Chemical Engineering Journal, 2023)

Preparation and characterization of a novel intelligent starch/gelatin binary film containing purple sweet potato anthocyanins for Flammulina velutipes mushroom freshness monitoring - Zihao Zong; Meng Liu; Hangjun Chen; Mohamed A. Farag; Weijie Wu; Xiangjun Fang; Ben Niu; Haiyan Gao (Food Chemistry, 2023)

Modified correction for predicting slip velocity of oil-water two-phase bubble flow in large-diameter pipes - Hao Qin; Xiangjun Liu; Meng Chen; Minjun Qin; Yang Pei; Zhongtao Wang; Kaiqiang Guo (Arabian Journal of Geosciences, 2021)

An Energy-Based Fatigue Damage Model for Sandstone Subjected to Cyclic Loading - Tiantao Li; Xiangjun Pei; Jian Guo; Minghui Meng; Runqiu Huang (Rock Mechanics and Rock Engineering, 2020)

Characterization of 36 insert/deletion mutations by STR genotyping method in grass carp, Ctenopharyngodon idella - Meng Zhang; Yubang Shen; Xiaoyan Xu; Rongquan Wang; Xiangjun Leng; Jiale Li (Conservation Genetics Resources, 2020)

Systematic analysis of long non-coding RNA and mRNA expression changes in ApoE-deficient mice during atherosclerosis - Xiaoqian Lou; Xiaoyan Ma; Dawei Wang; Xiangjun Li; Bo Sun; Tong Zhang; Meng Qin; Liqun Ren (Molecular and Cellular Biochemistry, 2019)
Atherosclerosis plays an important role in the pathology of coronary heart disease, cerebrovascular disease, and systemic vascular disease. Long non-coding RNAs (lncRNAs) are involved in most biological processes and are deregulated in many human diseases. However, the expression alteration and precise role of lncRNAs during atherosclerosis are unknown. We report here the systematic profiling of lncRNAs and mRNAs in an ApoE-deficient (ApoE − / − ) mouse model of atherosclerosis. Clariom D solutions for the mouse Affymetrix Gene Chip were employed to analyze the RNAs from control and ApoE − / − mice. The functions of the differentially expressed mRNAs and lncRNAs and the relationships of their expression with atherosclerosis were analyzed by gene ontology, co-expression network, pathway enrichment, and lncRNA target pathway network analyses. Quantitative real-time PCR (QRT-PCR) was used to determine the expression of mRNAs and lncRNAs. A total of 2212 differentially expressed lncRNAs were identified in ApoE − / − mice, including 1186 up-regulated and 1026 down-regulated lncRNAs (|FC| ≥ 1.1, p < 0.05). A total of 1190 differentially expressed mRNAs were found in the ApoE − / − mice with 384 up-regulated and 806 down-regulated (|FC| ≥ 1.1, p < 0.05). Bioinformatics analyses demonstrated extensive co-expression of lncRNAs and mRNAs and concomitant deregulation of multiple signaling pathways associated with the initiation and progression of atherosclerosis. The identified differentially expressed mRNAs and lncRNAs as well as the related signaling pathways may provide systematic information for understanding the pathogenesis and identifying biomarkers for the diagnosis, treatment, and prognosis of atherosclerosis.

Provenance of Cretaceous Dasheng Group Malanggou Formation in the mid-part of the Yishu fault zone, Shandong Province, China - Liguo Song; Guangzhou Mao; Mingping Cao; Xiaotong Liu; Pengrui An; Xiangjun Wang; Lingqiang Meng; Tieliang He; Yixin Dou (Arabian Journal of Geosciences, 2019)

Contributions of pore-throat size distribution to reservoir quality and fluid distribution from NMR and MIP in tight sandy conglomerate reservoirs - Meng Chen; Jiacai Dai; Xiangjun Liu; Yan Kuang; Minjun Qin; Zhongtao Wang (Arabian Journal of Geosciences, 2019)

Analysis of the Effects of a Rotating Rock on Rockfall Protection Barriers - Xin Qi; Xiangjun Pei; Rui Han; Yafeng Yang; Qingcheng Meng; Zhixiang Yu (Geotechnical and Geological Engineering, 2018)

Comparative analysis of the characteristics of extreme temperature changes between cities and mountains in China - Shengwei Zong; Zhengfang Wu; Jiawei Xu; Haibo Du; Xiangjun Meng; Lei Wang (Theoretical and Applied Climatology, 2015)

Quantitative relationships between precipitation and temperature over Northeast China, 1961–2010 - Haibo Du; Zhengfang Wu; Yinghua Jin; Shengwei Zong; Xiangjun Meng (Theoretical and Applied Climatology, 2013)

Characteristics of extreme daily minimum and maximum temperature over Northeast China, 1961–2009 - Haibo Du; Zhengfang Wu; Ming Li; Yinghua Jin; Shengwei Zong; Xiangjun Meng (Theoretical and Applied Climatology, 2013)

Estimating daily global solar radiation during the growing season in Northeast China using the Ångström–Prescott model - Zhengfang Wu; Haibo Du; Dongsheng Zhao; Ming Li; Xiangjun Meng; Shengwei Zong (Theoretical and Applied Climatology, 2012)

Extracting vegetation phenology metrics in Changbai Mountains using an improved logistic model - Ming Li; Zhengfang Wu; Lijie Qin; Xiangjun Meng (Chinese Geographical Science, 2011)

A comprehensive analysis of protein phosphatases in rice and Arabidopsis - Meng Yang; Shuhui Song; Guiming Liu; Kaifu Chen; Xiangjun Tian; Zhizhuang Joe Zhao; Songnian Hu; Jun Yu (Plant Systematics and Evolution, 2010)